2020
DOI: 10.1021/acschemneuro.0c00587
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Origin of Tau Protein Aggregation: Effects of Histidine Tautomerism on Tau267–312 Monomer

Abstract: Histidine tautomerism is considered a crucial component that affects the constitutional and accumulation characteristics of the tau 267−312 monomer in the neutral condition, which are connected with the pathobiology of Alzheimer's disease (AD). Interpreting the organizational characteristics and accumulation procedure is a challenging task because two tautomeric conformations (the N ε −H or N δ −H tautomer) can occur in the open neutral condition. In the current work, replica-exchange molecular dynamics (REMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…A similar helical region ( i.e. , 280–288) was also observed in another recent all-atom REMD simulation of the tau 267–313 segment . The PMF of R4 (Figure d) was similar to that of R1 and R2 (Figure b), with a broad free energy basin populated with various helical formations (snapshots 1, 2, 3, and 5 in Figure d).…”
Section: Resultssupporting
confidence: 79%
“…A similar helical region ( i.e. , 280–288) was also observed in another recent all-atom REMD simulation of the tau 267–313 segment . The PMF of R4 (Figure d) was similar to that of R1 and R2 (Figure b), with a broad free energy basin populated with various helical formations (snapshots 1, 2, 3, and 5 in Figure d).…”
Section: Resultssupporting
confidence: 79%
“…However, we examined these inter-residue contacts on the basis of the peptide main-chain (MC). The MC contour mapping of a macromolecule has been frequently utilized as a depiction of peptide secondary structure, an essential element in self-assembly and folding phenomena. , Figure exhibits a contact plot for the probability of inter-residual interactions at 308.09 K acquired from the last 100 ns of REMD trajectory analysis with less than 1.5 nm minimum distance between atoms. From the MC–MC contour map, thick bands along the main diagonal adjacent to residues D20–N29 were noticed in the δε and δδ isomers, which indicates a significant presence of α-helices near that region.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of PrP C into PrP Sc and its accumulation are largely dependent on several factors, including amino acid composition, pH, temperature, salt concentration, and the presence of lipids and metal ions. Another aspect that may have an important effect is histidine (His) tautomerization, which has been shown to play a key role in peptide aggregation. Diverse forms of His residues (namely, neutral and protonated) are correlated with organizational properties of different misfolded systems and can influence the accumulation pathways in peptides, leading to proteopathies. However, the intrinsic origin of PrP self-assembly due to diverse His behaviors remains largely undetermined. As misfolding of monomeric PrP and consequent oligomerization/fibrilization are closely connected to prion disease pathology, it is essential to examine the misfolding mechanism of the PrP monomer in the presence of His tautomerism .…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, a novel histidine tautomerism/protonation hypothesis accounting for the pathogenesis of AD and other neurological diseases has been suggested by our research team. 11–26 We have demonstrated that different protonated states in the histidine imidazole ring are related to the conformational characteristics of diverse misfolded peptides (namely Aβ, tau, amylin, and prion) and can influence fibrillization processes in polypeptides, resulting in proteopathies. This histidine hypothesis implies that protein accumulation may occur inherently rather than as a consequence of extrinsic agents.…”
Section: Introductionmentioning
confidence: 99%